TO COMPREHENSION OF THE CRITICAL THINKING NATURE: PHILOSOPHY OF HEART - Tiaglo, Oleksandr (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2024)
It is demonstrated in this research paper that in the 21st century, critical thinking is necessary in both peacetime and wartime. However, its condition cannot be considered satisfactory in Ukraine today. Therefore, the problem remains relevant: how to ensure that the education and effective functioning of critical thinking in our country finds reliable grounds and becomes regular? I proceed from the supposition that on the way to solve this problem, it is not sufficient to limit oneself only by careful study of the significant product of world thought and practice and literal duplication of what can be learned. It is necessary to reconsider carefully this learned in view of the relevant domestic traditions and realities of today’s life, to make it clearer and easier to accept by a wide public through a synthesis with related achievements of the national experience. This supposition determines my concrete goal – to find out what immanent achievements of Ukrainian philosophical thought should be relied on in order to contribute to a correct understanding of the critical thinking nature, and, further, to the organization of its proper education. To achieve this goal, part of the intellectual heritage of our philosophical genius – Hryhorii Skovoroda and its comments by Dmytro Chyzhevsky are considered in this research paper.It is argued that the domestic philosophy of heart, the key concept of which is "deep Heart" provides significant ground for correct understanding of the critical thinking nature, for the organization of its education. Conscious critical thinking should not be divided from the unconscious, in the terms of Skovoroda and Chyzhevsky – from the "Heart", the deepest "abyss" in a human, which generates and predetermines the "surface" of our psyche, so to speak. To a large extent, it is in the "deep Heart" that cognitive and affective dispositions are formed, which provide the necessary grounds for education, acceptation and regular fruitful functioning of critical thinking. It is not isolated from the influence of the "Heart" as a source of various emotions and feelings, which is grasped, in particular, by the contemporary concept of careful thinking.Education of a human with higher-order thinking, including real critical thinking, will be successful more probably when it begins not in university or high school, but in kindergarten at the latest. The content and form of delivering of critical thinking must be varied depending on the successive stages: the introductory stage, the stages of practice and integration, as well as the generalized transfer stage. It is claimed, within the last stage, the "cross-breading" of the typical in Ukraine university logic course and the world achievements in the field of critical thinking are rewarding.